Lexicogrammatical profiling of ASD: cognitive-functional mapping and diagnostic implications - Kato, Sumi; Hanawa, Kazuaki (Frontiers in Human Neuroscience, 2026)
IntroductionPrevious corpus-based study first established an annotated dataset of autism spectrum disorder (ASD) discourse, and subsequent modeling of lexicogrammatical patterns distinguished ASD from non-ASD discourse with high performance (accuracy 80%, precision 82%, sensitivity 73%, specificity 87%). That line of research further identified 46 statistically significant discriminators, of which 20 were analyzed in detail. The present study examines 18 additional discriminators and situates them within cognitive-functional domains to clarify their diagnostic relevance. Findings refine the language–cognition interface in ASD and extend the utility of lexicogrammatical profiling for assessment.MethodsThe Tag Linear Model was employed to identify lexicogrammatical features that distinguish ASD and non-ASD discourse. Logistic regression with 10,000 bootstrap iterations was applied to establish statistical significance. Although DNN models yielded higher predictive accuracy, the linear model provided transparent identification of discriminators.ResultsOf the 135 items analyzed, 46 were confirmed as statistically significant discriminators (p < 0.05). Eighteen of these, not previously examined, were analyzed in the present study. The discriminators were mapped onto 12 cognitive-functional domains, including working memory, executive functioning, joint attention, predictive processing, and weak central coherence. The results reveal distinctive patterns across multiple domains, including reduced use of benefactive auxiliaries, relational attributive clauses, obligation modality, evaluative and gradational resources, and mimetic onomatopoeia, reflecting systematic constraints in abstraction, perspective-taking, and pragmatic orientation.DiscussionThese findings demonstrate that choice patterns of lexicogrammar in ASD reflect domain-specific cognitive constraints. Interpreting the 18 discriminators within 12 cognitive-functional domains provides a linguistically grounded perspective on the neurocognitive profile of ASD and offers implications for future diagnostic and intervention research.